Two Negative-Strand RNA Viruses Identified in Watermelon Represent a Novel Clade in the Order Bunyavirales - Xin, Min; Cao, Mengji; Liu, Wenwen; Ren, Yingdang; Zhou, Xueping; Wang, Xifeng (Frontiers in Microbiology, 2017)
Two novel negative-sense, single-stranded (ss) RNA viruses were identified in watermelon plants and named watermelon crinkle leaf-associated virus 1 and 2 (WCLaV-1 and -2), respectively. The multipartite genomes consist of three RNA molecules of approximately 6.8, 1.4 and 1.3 kb. The genomes and the deduced proteins of RNA1 and RNA3 show features resembling those of members in the genus Phlebovirus and Tenuivirus; however, the predicted proteins encoded by RNA2 are related to the movement protein (MP) in the genus Ophiovirus and Emaravirus. Furthermore, these two viruses define a novel clade in the family Phenuiviridae, order Bunyavirales, which is phylogenetically related to the viruses in the above four genera. Moreover, after mechanical inoculation with WCLaV-1 seedlings of the natural host watermelon plants develop crinkling similar to those observed in the field. These findings enhance our understanding of the evolution and the classification of ssRNA viruses.